Plasma Spray vs. Electrochemical Deposition: Toward a Better Osteogenic Effect of Hydroxyapatite Coatings on 3D-Printed Titanium Scaffolds - Sun, Yang; Zhang, Xing; Luo, Mingran; Hu, Weifan; Zheng, Li; Huang, Ruqi; Greven, Johannes; Hildebrand, Frank; Yuan, Feng (Frontiers in Bioengineering and Biotechnology, 2021)
Surface modification of three-dimensional (3D)-printed titanium (Ti) scaffolds with hydroxyapatite (HA) has been a research hotspot in biomedical engineering. However, unlike HA coatings on a plain surface, 3D-printed Ti scaffolds have inherent porous structures that influence HA coatings' characteristics and osteointegration. In the present study, HA coatings were successfully fabricated on 3D-printed Ti scaffolds using plasma spray and electrochemical deposition, named plasma-sprayed HA (PSHA) and electrochemically deposited HA (EDHA), respectively. Compared to EDHA scaffolds, HA coatings on PSHA scaffolds were smooth and continuous. In vitro cell studies confirmed that PSHA scaffolds have a better potential for promoting adhesion, proliferation, and osteogenic differentiation of bone mesenchymal stem cells than EDHA scaffolds at the early and late stages. Moreover, in vivo studies showed that PSHA scaffolds were endowed with superior bone repair capacity. Although EDHA technology is simpler and more controllable, its limitation due to the crystalline and HA structures needs to be improved in the future. Thus, we believe plasma spray is a better choice for fabricating HA coatings on implanted scaffolds, which may become a promising method for treating bone defects.